Frequency‐Domain Response Analysis for Quantitative Systems Pharmacology Models. (29th November 2017) - Schulthess, Pascal; Post, Teun M.; Yates, James; van der Graaf, Piet H.
Abstract : Drug dosing regimen can significantly impact drug effect and, thus, the success of treatments. Nevertheless, trial and error is still the most commonly used method by conventional pharmacometric approaches to optimize dosing regimen. In this tutorial, we utilize four distinct classes of quantitative systems pharmacology models to introduce frequency‐domain response analysis, a method widely used in electrical and control engineering that allows the analytical optimization of drug treatment regimen from the dynamics of the model.